Application of Hydroxytriazenes in Corrosion Protection of Brass - S. Kumar; Meenakshi Garg; N. S. Chundawat; J. S. Jodha; Peeyush Patel; A. K. Goswami (E-Journal of Chemistry)
Three hydroxytriazenes have been screened for their inhibitive action against corrosion of brass in ammoniacal environment. They have been found to possess 31.43 to 80.77%. Percentage inhibitive efficiency at 7.5 to 12 N ammonia solutions. The results indicate that hydroxytriazenes can further be explored for corrosion inhibitive property